If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(2x + -4) = -13 + -1x Reorder the terms: -8(-4 + 2x) = -13 + -1x (-4 * -8 + 2x * -8) = -13 + -1x (32 + -16x) = -13 + -1x Solving 32 + -16x = -13 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 32 + -16x + x = -13 + -1x + x Combine like terms: -16x + x = -15x 32 + -15x = -13 + -1x + x Combine like terms: -1x + x = 0 32 + -15x = -13 + 0 32 + -15x = -13 Add '-32' to each side of the equation. 32 + -32 + -15x = -13 + -32 Combine like terms: 32 + -32 = 0 0 + -15x = -13 + -32 -15x = -13 + -32 Combine like terms: -13 + -32 = -45 -15x = -45 Divide each side by '-15'. x = 3 Simplifying x = 3
| F=13fgh | | 7x+26=-3x+4(x+2) | | 14+5x=13+6x | | 6g-18g= | | 5r^2+20r+18=3 | | 18=-6(3x+15) | | 8x^3-4x^2-12x=0 | | 4/n+9=2/7 | | K-6k= | | 6x-x=5 | | 5x+5(-7x+16)=160 | | a^2-20a+44=0 | | 8(5x-9)= | | 20-5x=4+3x | | 7(-5r-8)-r=-236 | | 6+7x=180 | | Y=2.5x-40 | | 22m+6n+(4m-8)=26m+6n+8 | | 35=9(6a-7) | | 3y+y^2-10= | | -130.3005=3.3(5.05r-0.6) | | m^2-6m-51=0 | | -(-8x-3)-x=4x+6(-5+x) | | 2x+75=3x | | -2a-3b= | | 6x+8x-54=90-4x | | 13+(14+x)= | | 7x-3x=9+4x-9 | | -5h+15+7h+17= | | 8w+16=4(7+2w)+3 | | 5x^3+70x^2+240x=0 | | 30h+70=140 |